Using mobile Facebook as an LMS: exploring impeding factors - Gabarre, Serge; Gabarre, Cecile; Din, Rosseni; Mohd Shah, Parilah; Abdul Karim, Aida (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present article describes exploratory research conducted in two French language courses to identify the impeding factors of using a social networking site (SNS) on smartphones. Following the replacement of the faculty’s learning management system (LMS) by a unified platform, there were difficulties in conducting the same class activities that the researchers and students had grown accustomed to. Students were no longer able to initiate discussions in the target language in online forums nor were they able to use their mobile devices to access and share resources directly from the classroom. Current literature emphasises (1) the benefits of learning on SNS and (2) the advantages of mobile learning, which suggests these technologies as possible solutions to the issue discussed in the present study. The opportunities afforded by these technologies were first explored with a survey and deeper knowledge was gained with group interviews. Descriptive statistics were used to analyse the survey data while computer aided qualitative analysis software was used to categorise the themes which emerged from the interviews. Smartphone ownership and SNS membership were not identified as impeding factors to adopt these tools for learning. However, several impeding factors were identified with each technology. Inhibiting issues with SNS were: the lack of privacy, the dichotomy in the notion of friendship, and paradoxically the lack of stimulus to communicate. The constraints from the mobile phones stemmed from their intrusive nature and their inability to perform the same tasks as laptops. These findings are assessed and discussed in light of other research before an SNS and smartphone system is implemented to supersede or replace the LMS.